Bridge connection between depression and anxiety symptoms and lifestyles in Chinese residents from a network perspective - Wang, Shi-Bin; Xu, Wen-Qi; Gao, Li-Juan; Tan, Wen-Yan; Zheng, Hui-Rong; Hou, Cai-Lan; Jia, Fu-Jun (Frontiers in Psychiatry, 2023)
Background: Lifestyle habits are vital components of the culture of mental health treatment settings. We examined bridge connection between depressive and anxiety symptoms and lifestyles from a network perspective using a population-based study. Methods: Face-to-face interviews were conducted with a provincially representative sample of 13,768 inhabitants from the Guangdong Sleep and Psychosomatic Health Survey based on standardized evaluation techniques. We identified the central symptoms by expected influence. The interconnection between depression and anxiety symptoms, as well as bridge connectivity linking depression-anxiety symptoms and lifestyle factors were assessed using bridge centrality index. Network stability and sensibility analyses were performed using a case dropping bootstrap procedure. Results: The core symptom who exhibited the highest expected influence was fatigue or little energy, followed by uncontrollable worry, trouble relaxing and sad mood in the depression-anxiety symptoms network, while guilt was the most interconnected symptom and had the highest bridge strength. Surrounding nodes of each node explained an average variance of 57.63%. Additionally, suicidal thoughts were recognized as collective bridging symptoms connecting lifestyle variables in the network integrating depression-anxiety symptoms with lifestyle factors. Current tobacco and alcohol consumption were positively associated with suicidal thoughts and irritability. Habitual diet rhythm and physical exercise frequency were linked to suicidal thoughts, guilt and poor appetite or overeating. Suicidal thoughts, irritability and guilt indicated the greatest connectivity with lifestyle factors. All networks had high stability and accuracy. Conclusions: These highlighted core and bridge symptoms could serve as latent targets for prevention and intervention of comorbid depression and anxiety. It might be crucial for clinical practitioners to design effective and targeted treatment and prevention strategies aiming at specific lifestyles and behaviors.